Teens and Dating: Tips for Parents and Professionals - Kate Fogarty (EDIS, 2006)
FCS-2250, a 5-page fact sheet by Kate Fogarty, is one in a series of discussions on understanding teen sexuality. This publication helps parents and educators understand the pros and cons of dating in order to help them communicate effectively with teens. Published by the UF Department of Family Youth and Community Sciences, October 2006.